Menumbuhkan Nilai-Nilai Moderasi Beragama Pada Santri (Studi Pada Pondok Tahfidz Yanbu’ul Qur’an Kudus) - Amin, Muhammad; Kholiq, Nor; Ristiyana, Sri Farida (Jurnal Penelitian, 2022)
This research aims to describe the efforts of Islamic boarding school in fostering moderation values for santri, to find out the anticipation of Islamic boarding school in counteracting intolerant understanding in santri and the surrounding community, and to know the extent to which the values of moderation are applied in Islamic Boarding School Tahfizd Yanbu'ul Qur'an Menawan Kudus. The uniqueness of this study lies in the location of the Islamic boarding school which is a tahfizd boarding school with a conservative educational base that has a culture that is able to foster religious moderation values in students.  The method used is a qualitative-descriptive approach that uses observational data, interviews and documentation studies which are then analyzed using the descriptive technique of the Miles and Hubermen model.  This study succeeded in finding that although pesantren is classified as a conservative religious education institution, the values of religious moderation are always grown with various efforts, namely: programmed internalization in the form of moderation-based learning materials, habituation activities such as praying in congregation, mutual cooperation, tawadlu’ towards teachers and foreign language week activities.  Then internalization is not programmed in the form of appeals and role models by asatidz, punishments for those who violate and direct implementation.